IMPACT OF EDUCATION ON SELF-RELIANCE AND WEALTH CREATION AS PERCEIVED BY CORP MEMBERS IN SOKOTO STATE, NIGERIA - AYUBA PhD, Iya, H.; PUR, Hamsatu, J.; YAKUBU, Wisdom (Journal of Professional Counselling, 2025)
This study; Impact of Education on Self-Reliance and Wealth Creation as perceived by serving Corp members in Sokoto State, Nigeria focused on investigating the extent to which graduates of tertiary institutions in Nigeria are self-reliant and their ability to create wealth. It was survey research with two objectives and corresponding questions guided the study. The population used comprised graduates from different tertiary institutions in Nigeria, who are serving Corp members in Sokoto State as at August, 2024. A total of 74 Corp members voluntarily participated in this exercise, and by convenient sampling, all 74 of them constituted the sample used. A 33 item instrument titled; Self-reliance and Wealth Creation Ability Scale (SRWCAS) was adapted by the researchers. It has 0.76 validity index and α= 0.75 coefficient of reliability using Cronbach alpha. Statistics used for data analyses include mean, standard deviation, and chi-square. Among the results obtained are; tertiary education in Nigeria equips graduates with skills and knowledge to a very high extent but promotes more self-reliance than it equips learners with wealth creation skills. Also, all category of graduates who responded to the instrument had high self-reliance ability however, graduates of specialized Universities scored a bit higher than their counterparts from other tertiary institutions in wealth creation ability. It was therefore concluded that lecturers in tertiary institutions across Nigeria should intensify efforts in helping learners understand how to translate the knowledge they acquire to real life wealth creation competences that translate to economic independence/self-reliance.